2021
DOI: 10.1111/1750-3841.15971
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus alleviated obesity induced by high‐fat diet in mice

Abstract: Obesity is closely related to dyslipidaemia, diabetes and other metabolic syndromes. Long-term consumption of a high-fat diet (HFD) is an important risk factor that can lead to obesity. In the current research, three Lactobacillus strains, namely, Loigolactobacillus coryniformis subsp. torquens T3 (T3), Lacticasebacillus paracasei subsp. paracasei M5 (M5), and Lacticaseibacillus paracasei subsp. paracasei X12 (X12), were tested to determine their inhibitory effects on HFD-induced obesity. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…SCFAs increased the relative abundance of Chlamydia and Lactobacillus and decreased the relative abundance of Bacteroides, Romboutsia, Lactococcus and Alloprevotella. Consistent with previous studies, the increase in Chlamydia is associated with obesity-related metabolic syndrome, and the increase in Lactobacillus can reverse obesity induced by HFD and regulate the microbiological SCFAs hormone pathway to regulate metabolism (43,44). The increase in Bacteroides abundance is related to the level of estradiol (18).…”
Section: Discussionsupporting
confidence: 87%
“…SCFAs increased the relative abundance of Chlamydia and Lactobacillus and decreased the relative abundance of Bacteroides, Romboutsia, Lactococcus and Alloprevotella. Consistent with previous studies, the increase in Chlamydia is associated with obesity-related metabolic syndrome, and the increase in Lactobacillus can reverse obesity induced by HFD and regulate the microbiological SCFAs hormone pathway to regulate metabolism (43,44). The increase in Bacteroides abundance is related to the level of estradiol (18).…”
Section: Discussionsupporting
confidence: 87%
“…2 A). According to previous studies reporting a decrease in the Chao1 index-related diversity associated with HFD intake ( Campbell et al, 2019 , Song et al, 2021 ), our results showed that, when compared with the ND group, HFD intake modified the microbial diversity and, among the tested compounds, 6-gingerol changed the abundance of certain bacteria over two weeks, suggesting a disrupted gut environment.
Fig.
…”
Section: Resultssupporting
confidence: 78%
“…Prior studies have also showed that specific gut microbiota modulation and presence of beneficial species into the gut, as measured through an increased Bacteroidetes/Firmicutes ratio, improves leptin response [ 42 ]. More specifically, species that are common in probiotics, such as Bifidobacterium and Lactobacillus, had beneficial effects on leptin sensitivity and were found to be decreased overall in leptin-deficient mice [ 43 , 44 ]. Therefore, it appears that the effects of gut microbiota on leptin responses is dependent on specific species as well as gut enterotypes, which can be altered by depletion or addition of probiotics.…”
Section: Discussionmentioning
confidence: 99%